Non-Hermitian photonics promises exceptional topology of light - Bikashkali Midya (Nature Portfolio, 2018)
Abstract The band degeneracy, either the exceptional point of a non-Hermitian system or the Dirac point associated with a topological system, can feature distinct symmetry and topology. Their synergy will further produce more exotic topological effects in synthetic matter.